2021
DOI: 10.1039/d1nj01143j
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and computational look at the radiolytic degradation of TODGA and the effect on metal complexation

Abstract: Diglycolamide extractants, and in particular N,N,N’N’- tetraoctyl diglycolamide (TODGA), are currently under investigation for use in nuclear fuel reprocessing by liquid-liquid separations. Several processes, such as ARTIST, i-Sanex, and EURO-GANEX...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 83 publications
5
24
0
Order By: Relevance
“…Overall, the identified radiolysis products are identical to the ones formed when irradiating DGA solutions without metallic ions with gamma rays. 23,27,28,33,37,39,41,42,45,46,59 As after gamma irradiation of TODGA solution without metallic ions, DPXIII has not been observed alone in the solution. It has, however, been observed complexed to Am (Table 5).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Overall, the identified radiolysis products are identical to the ones formed when irradiating DGA solutions without metallic ions with gamma rays. 23,27,28,33,37,39,41,42,45,46,59 As after gamma irradiation of TODGA solution without metallic ions, DPXIII has not been observed alone in the solution. It has, however, been observed complexed to Am (Table 5).…”
Section: Resultsmentioning
confidence: 96%
“…Fukui functions can be used to determine the likely sites for electrophilic, nucleophilic, or radical attack on a molecule 59,75,76 The Fukui function used is composed of 3 separate equations listed as follows:…”
Section: Computational-fukui Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the presence of nitric, the formation of aggregates, adducts and different conformers of the diglycolamide are of particular interest. 52 …”
Section: Resultsmentioning
confidence: 99%
“… 43 Also Kimberlin et al reported a slight protective effect of nitric acid. 52 For CMPO, nitric acid showed a strong protective effect. 49 …”
Section: Introductionmentioning
confidence: 97%